Role of Judiciary in Protecting Rights of the Prisoners in India: An analysis of the Indian judiciary's role in protecting prisoners' rights (Journal of Advances and Scholarly Researches in Allied Education, 2018)
It is critical for our nation's courts to safeguard the rights of prisoners. Of course, the IndianSupreme Court is hailed as a guiding light for human rights against torture. By interpreting Article article21, the Hon. Indian Supreme court created human rights philosophy for the preservation defence ofprisoners' rights to human dignity. In order to determine the feelings held and fresh tactics developed bythe Indian court to guarantee the preservation of the prisoners' human rights, this article carefullyexamines and scrutinises the major judgments handed down by higher judiciary in India.